Aberrant astrocytic expression of chondroitin sulfate proteoglycan receptors in a rat model of amyotrophic lateral sclerosis. Issue 2 (28th July 2017) - Shijo, Tomomi; Warita, Hitoshi; Suzuki, Naoki; Kitajima, Yasuo; Ikeda, Kensuke; Akiyama, Tetsuya; Ono, Hiroya; Mitsuzawa, Shio; Nishiyama, Ayumi; Izumi, Rumiko; Aoki, Masashi
Abstract: Amyotrophic lateral sclerosis (ALS) is a fatal neurodegenerative disease. Progressive and systemic loss of motor neurons with gliosis in the central nervous system (CNS) is a neuropathological hallmark of ALS. Chondroitin sulfate proteoglycans (CSPGs) are the major components of the extracellular matrix of the mammalian CNS, and they inhibit axonal regeneration physically by participating to form the glial scar. Recently, protein tyrosine phosphatase sigma (PTPσ) and leukocyte common antigen‐related protein were discovered as CSPG receptors that play roles in inhibiting regeneration. Here we examined the expression of CSPG receptors in transgenic female rats overexpressing an ALS‐linked mutant cytosolic Cu/Zn superoxide dismutase gene ( SOD1 ). In contrast to controls, multiple immunofluorescence analyses revealed aberrant expression of CSPG receptors dominantly in reactive astrocytes, while PTPσ expression in neurons decreased in the spinal ventral horns of ALS transgenic rats. The aberrant and progressive astrocytic expression of CSPG receptors and reactive astrocytes themselves may be therapeutic targets for reconstructing a regeneration‐supportive microenvironment under neurodegenerative conditions such as ALS. Abstract : The vimentin‐positive reactive astrocytes express chondroitin sulfate proteoglycan (CSPG) receptors in spinal ventral horns of amyotrophic lateral sclerosis (ALS) model rats, suggesting that CSPG receptors and reactive astrocytes are involved in CSPG homeostasis under ALS‐like neurodegenerative condition.